Baicalein impairs vascular tone in normal rat aortas: role of superoxide anions - Machha, A.; Achike, F.I.; Mohd, A.M.; Mustafa, Mohd Rais (Elsevier, 2007)
Acute exposure to the flavonoid baicalein inhibited endothelium-dependent relaxation in physiological arteries, although the mechanisms are not fully understood. We investigated the effect of baicalein on vascular tone in Wistar–Kyoto (WKY) rat isolated aortic rings in the presence and absence of oxidative stress to further determine the underlying mechanisms. Exposure to baicalein (10 μM) completely abolished endotheliumdependent relaxation induced by acetylcholine and attenuated significantly the endothelium-independent relaxation induced by sodium nitroprusside. Baicalein, similar to Nω-nitro-L-arginine methyl ester (L-NAME, 10 μM), potentiated significantly the contractile response of aortic rings to α1-adrenoceptor agonist phenylephrine. In the presence of L-NAME the baicalein effect on phenylphrine contraction or acetylcholine relaxation was unaltered, suggesting that these effects of baicalein are (like L-NAME effect) endothelial nitric oxide synthase (eNOS)/ endothelium-derived nitric oxide-dependent. Inhibition of cyclooxygenase activity with indomethacin (10 μM) or scavenging of superoxide anions with superoxide dismutase (150 units/ml), but not scavenging of hydrogen peroxide with catalase (800 units/ml), enhanced significantly by an essentially similar extent the relaxation to acetylcholine in baicalein-pretreated aortic rings. Relaxant effect to acetylcholine was significantly attenuated in control aortic rings, but was completely abolished in baicalein-pretreated aortic rings in the presence of reduced form of β- nicotinamide adenine di-nucleotide (β-NADH, 300 μM). Baicalein blocked β-NADH (300 μM)-induced transient contractions, suggesting that baicalein may have inhibited activity of NADH/NADPH-oxidase. Baicalein did not alter the failure of acetylcholine to induce relaxation in the presence of pyrogallol (300 μM). In summary, acute exposure to baicalein impairs eNOS/endothelium-derived nitric oxide-mediated vascular tone in rat aortas through the inhibition of endothelium-derived nitric oxide bioavailability coupled to reduced bioactivity of endothelium-derived nitric oxide and to cyclooxygenase-mediated release of superoxide anions.